Valuation of treatments for rare diseases: a systematic literature review of societal preference studies - Dabbous, O; Chachoua, L; Aballéa, S; Sivignon, M; Persson, U; Petrou, S; Richardson, J; Simoens, S; Toumi, M (Springer, 2022)
Introduction: We sought to synthesize published empirical studies that elicited and characterized societal valuations of orphan drugs and the attributes that may drive different valuations for orphan drugs versus other treatments.